MENCIPTAKAN NILAI TAMBAH PADA USAHA PIALANG ASURANSI GUNA MEMPENGARUHI CALON TERTANGGUNG MEMBELI ASURANSI - Awaloedin, Mulawarman; Robidi (UM. Bengkulu, 2025)
Changes in the business landscape must be accompanied by changes in the behaviour of insurance brokers. For this reason, this research attempts to measure aspects that were not measured in the previous general context. Through a quantitative approach with an applied survey method, this research aims to uncover the phenomenon of brokers who work with high commitment and performance. Through a series of measurement tools, sixteen brokers have responded to a number of measurement tools. It was found that the mindset, desire/will and obsession of the brokers were not too high, so the monthly and annual targets set were also not too high. Keywords: insurance broker; mindset; obsession; passion